Investigation on demand-based chiller optimization - Ler, Han Qiang (2014)
Buildings in Singapore are one of the major contributor of carbon footprint. This sector in particular consumes large amount of electricity. Most of these electricity consumption are by air conditioning equipment which is essential in providing thermal comfort in the hot and humid climate region. As Singapore progressively pushes itself to decrease the nation’s carbon footprint, studies looking into reducing the main electricity consumers are necessary. Simulation tools such as TRNSYS are able to model after real buildings, Singapore’s weather and cooling equipment based on past data and mathematical models in the software. In this study, a typical 20-storey office building with a constant mixed air distribution water-cooled chilled water chiller plant is modelled. A parametric study of the chiller plant is then performed. Based on the simulations, savings of up to 19% is demonstrated as compared to conventional constant mixed air distribution water-cooled chilled water chiller plant system.